Characterization of macrolide resistance of Mycoplasma pneumoniae in children in Shenzhen, China. Issue 7 (17th July 2013) - Ma, Zhuoya; Zheng, Yuejie; Deng, Jikui; Ma, Xiaoli; Liu, Hui
Summary Macrolide‐resistant Mycoplasma pneumoniae (MR‐M. pneumoniae) was isolated from clinical specimens in Shenzhen, China from November 2010 to July 2011. A comparative study was conducted to determine whether macrolides are effective in treating patients infected with MR‐M. pneumoniae. Of 57 M. pneumoniae strains, 36 harbored point mutations on A2063G in the 23S ribosomal RNA gene. A total of 36 (63%) strains were classified as MR‐M. pneumonia and 21 (37%) as macrolide‐susceptible M. pneumoniae (MS‐M. pneumoniae). The clinical courses of MR‐M. pneumoniae‐infected patients (MR patients) treated with macrolides were compared with those of MS‐M. pneumoniae‐infected patients (MS patients). The patient demographics (sex, age), most laboratory findings, and diagnosis did not show significant differences between the two groups. The MR patients had higher mean total febrile days compared with MS patients (6.56 ± 6.17 days vs. 3.57 ± 3.80 days, P = 0.05). The MR patients were more likely to be have levels of high‐sensitivity C‐reactive protein than MS patients (42% (15/36) vs. 14% (3/21), P = 0.03). Although the febrile period was prolonged in MR patients treated with macrolides, the fever resolved even when the initial prescription was unchanged. Therefore, these results suggest that macrolides are less effective in MR patients than in MS patients. Pediatr Pulmonol. 2014; 49:695–700. © 2013 Wiley Periodicals, Inc.